Training the Lower Body for Better Stances, Steps, & Kicks (Revista de Artes Marciales Asiáticas, 2012)
The purpose of this article is to present various training methods for the lower body thereby making them immediately available to the readers to further their own training. The lower body will be defined generally as the region of the body from the waist (area between short rib and hip bone) downward. The training methods presented will work along two major lines of reference—that of time or history i.e. modern methods verses traditional methods, and that of geography and culture or “East verses West.” For reading ease, the presentation will follow a sequence going from ideas more common to martial arts practitioners to less common ideas. In this way a reader can bridge familiar and unfamiliar concepts without losing orientation to the main theme.